Restoring the Forest—Restoring the State: An Essay on Forestation - Konczal, Agata A. (Porównania, 2022)
This article looks at the state/forest relationship and how and when the state creates discourses about the forest to serve its current objectives and policies. It is a case study of the Polish state and its approach to forest restoration practices. Looking at past actions since 1918 through which the Polish state has restored the forest, the text traces the discursive practices of forest nationalisation. Combining historical perspectives with contemporary discussions of forest restoration within the European Union and global institutions, the text offers an analysis of the power relations inscribed and embodied in nature management activities. The text touches upon a broader reflection on nature management and the power relations inscribed and embodied within it and examines how “the environment” and environmental issues have been constructed as domains requiring state regulation and protection. Focusing on planting rather than deforestation, the article describes the use of environmental governance policy tools to maintain power over discursive and material actions in relation to the landscape by states and/or international institutions. This article is framed within environmental politics, combined with environmental history and anthropology.